Assessing Whatapp for Communication in A Youth Organization: A Dual Method Approach - Ugoala, Bibian (Universitas Negeri Makassar, 2021)
Communication is pertinent to the existence of all human endeavours. Without communication, most sectors of our endeavours may be deformed. This study assesses the impact of communication among diocesan youth executives of the Anglican Youth Fellowship (AYF) in the Diocese of Abuja. The scholars employed the dual methodology in conducting the study. Eighteen (18) executives from the diocese were interviewed and surveyed. Findings from the study reveal that the Anglican Youth Fellowship (AYF) Diocese of Abuja to a large extent uses WhatsApp for communication purpose. It was also found that the affordability and ease of use of the application motivate the youth executives to use WhatsApp. The overarching themes that emerged in the qualitative study include ease of communication and manipulation, cost-effectiveness, purpose tailored, closely-knitted, distraction. Revelations from the quantitative survey show that a higher percentage of the respondents affirm that WhatsApp is a preferred tool for communication. The study is anchored on Media Richness Theory (MRT). Despite the gains of WhatsApp, albeit, the research found that there are distractions in the communication flow due to the sharing of unsolicited contents on the group, which may derail conversion. The study concludes that WhatsApp has proved to be useful in the youth organization.